PENYELESAIAN KREDIT MACET TANPA AGUNAN PADA PERJANJIAN PEMBERIAN BANTUAN DALAM PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN (PNPM-MP) KABUPATEN DHAMASRAYA - Vivi Amelia; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The National Program for Rural Community Empowerment (PNPM-MP) is a program to increase poverty in the form of revolving aid for Small and Medium Enterprises (MSMEs) in the form of Savings and Loans for Women (SPP). Provision of revolving loans to the poor through Self-Help Groups (SHGs), where the community groups apply for loans in the form of SPP. The advantage of this program is the non-imposition of collateral as a condition to enter into credit agreements. Unsecured loans are highly vulnerable to default. The purpose of this thesis namely; First, the factors causing the debtor to default on PNPM-MP Sungai Rumbai District. The second problem solving to the debtor who has been performing in PNPM-MP of Sungai Rumbai Sub-district. The type of research to be used is Sociological research, Sociological research is a study that examines the legal aspects by looking at applicable legislation and comparing with the implementation of the field survey. The location of research conducted PNPM-MP located in District River Rumbai Regency Dharmasraya West Sumatra. Sources of data used are primary, secondary and tertiary legal data, data collecting techniques in this study with observation, interview and literature study.The result of this research is concluded that the factors causing bad credit in PNPM-MP Sungai Rumbai sub-district that the writer get consist of: Factors derived from the manager (UPK) PNPM-MP Sungai Rumbai, First, the manager is not careful in analyzing the loan application of the prospective debtor. Second, the excessive credit granting of the debtor's needs. Third, the lack of credit supervision is given. Factors derived from the debtor itself, namely: First, family economic factors. Second, business factors. Third, the debtor factor is not well-intentioned. And factors that come from external outside the ability of PNPM-MP and KSM: First, the decline in selling prices of plantation products. Secondly, the disaster that struck the debtor's business. Efforts to solve the problem of the debtor making the default: First, rescheduling. Second, Reconditioning. PNPM-MP Sungai Rumbai does not go through the process of seizure / procurement of general security in non-performing loans and through legal process even though there is a written provision in the Letter of Agreement of SPP Revolving Loan Payment. UPKs solve non-performing loans by only being solved by village deliberations or in a familial manner that is considered not to cause problems by either the Manager or the Authority Holder.Keywords: Credit Agreement, Bad Credit and PNPM-MP